Math Problem Statement

Inverse of f(X)=-x^2+4x-4 for x is less than or equal to 2

Solution

To find the inverse of the function f(x)=x2+4x4f(x) = -x^2 + 4x - 4 for x2x \leq 2, we need to follow these steps:

1. Express the function as y=f(x)y = f(x):

y=x2+4x4y = -x^2 + 4x - 4

2. Solve for xx in terms of yy:

We need to solve the quadratic equation for xx in terms of yy.

x2+4x4=y-x^2 + 4x - 4 = y

To make it easier to solve, multiply both sides by -1:

x24x+4=yx^2 - 4x + 4 = -y

This simplifies to:

x24x+(4+y)=0x^2 - 4x + (4 + y) = 0

Now, this is a standard quadratic equation in the form ax2+bx+c=0ax^2 + bx + c = 0, where a=1a = 1, b=4b = -4, and c=4+yc = 4 + y.

3. Use the quadratic formula to solve for xx:

The quadratic formula is:

x=b±b24ac2ax = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}

Substituting a=1a = 1, b=4b = -4, and c=4+yc = 4 + y:

x=4±164(1)(4+y)2(1)x = \frac{4 \pm \sqrt{16 - 4(1)(4 + y)}}{2(1)}

Simplify the expression under the square root:

x=4±16164y2x = \frac{4 \pm \sqrt{16 - 16 - 4y}}{2}

x=4±4y2x = \frac{4 \pm \sqrt{-4y}}{2}

x=4±2iy2x = \frac{4 \pm 2i\sqrt{y}}{2}

However, because we are dealing with real values of yy and we need xx to be real (since y=f(x)y = f(x) and we're only considering x2x \leq 2), there must be an issue with the sign or approach.

Let's rewrite the equation:

4. Refactor to avoid complex values:

Rewriting the original function in a completed square form:

f(x)=(x24x+4)f(x) = -(x^2 - 4x + 4) f(x)=(x2)2f(x) = -(x - 2)^2

So, we have:

y=(x2)2y = -(x - 2)^2

(x2)2=y-(x - 2)^2 = y

Solving for xx:

(x2)2=y(x - 2)^2 = -y

Taking the square root on both sides:

x2=±yx - 2 = \pm \sqrt{-y}

Since y\sqrt{-y} must be a non-negative value and the function is defined for real values, we take the negative square root due to the restriction x2x \leq 2:

x2=yx - 2 = -\sqrt{-y}

Finally, solve for xx:

x=2yx = 2 - \sqrt{-y}

5. Express the inverse function:

Thus, the inverse function f1(y)f^{-1}(y) is:

f1(y)=2y, for y0f^{-1}(y) = 2 - \sqrt{-y}, \text{ for } y \leq 0

Summary:

The inverse function is:

f1(y)=2yfory0f^{-1}(y) = 2 - \sqrt{-y} \quad \text{for} \quad y \leq 0


Would you like more details or have any questions? Here are some related questions:

  1. How can you verify if two functions are inverses of each other?
  2. What is the domain and range of the original function f(x)f(x)?
  3. How does the restriction x2x \leq 2 affect the inverse function?
  4. What is the graphical interpretation of finding an inverse?
  5. How would you find the inverse if the function was defined for x>2x > 2?

Tip: Always ensure the domain of the original function aligns with the range of the inverse function.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Inverse Functions
Quadratic Equations

Formulas

Quadratic formula

Theorems

-

Suitable Grade Level

Grades 10-12